2023
DOI: 10.3389/fnut.2023.1185047
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in exploring and exploiting soybean functional peptides—a review

Abstract: Soybeans are rich in proteins and phytochemicals such as isoflavones and phenolic compounds. It is an excellent source of peptides with numerous biological functions, including anti-inflammatory, anticancer, and antidiabetic activities. Soy bioactive peptides are small building blocks of proteins that are released after fermentation or gastrointestinal digestion as well as by food processing through enzymatic hydrolysis, often in combination with novel food processing techniques (i.e., microwave, ultrasound, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…The results obtained indicated that LSE might exert a protective effect against oxidative stress in H. pylori infected cells that could be attributed to protein/peptides or other bioactive compounds contained in the soybean extract. The antioxidant effects of lunasin and other soybean peptides have been previously reported in different cell and animal models, but not in H. pylori-infected cells [40,41]. Furthermore, other compounds present in LSE and not determined in this work could contribute to the reduction of ROS production by the cells.…”
Section: Antioxidant and Anti-inflammatory Activity Of Lsementioning
confidence: 56%
See 1 more Smart Citation
“…The results obtained indicated that LSE might exert a protective effect against oxidative stress in H. pylori infected cells that could be attributed to protein/peptides or other bioactive compounds contained in the soybean extract. The antioxidant effects of lunasin and other soybean peptides have been previously reported in different cell and animal models, but not in H. pylori-infected cells [40,41]. Furthermore, other compounds present in LSE and not determined in this work could contribute to the reduction of ROS production by the cells.…”
Section: Antioxidant and Anti-inflammatory Activity Of Lsementioning
confidence: 56%
“…It provoked a significant reduction of 6.71% in the levels of IL-8 produced by AGS cells (Figure 7B). The anti-inflammatory activity of the peptide lunasin is associated with a suppression of NF-κB pathway by its reduction on the release of cytokines such as IL-1, IL-6 and IL-8 and also the ability of inhibiting integrins [41], another important mechanism in H. pylori infection. Although there are no studies conducted in H. pylori-infected cells with the protein fraction of soybeans, bioactive compounds from sprouted soybeans digest reduced in 19.5% the release of IL-8 in Caco-2 cells [44].…”
Section: Antioxidant and Anti-inflammatory Activity Of Lsementioning
confidence: 99%
“…Further research should focus on developing efficient extraction and purification methods to enhance the practical utility of these sweet peptides. Testing in various food matrices will reveal the optimal conditions for their integration into commercial products [29]. In vivo studies should confirm their safety and efficacy as sweeteners to meet regulatory standards.…”
Section: Electronic Tongue Analysismentioning
confidence: 99%
“…Its financial and nutritional value is attributed to a high protein range, a balanced, vital amino acid profile, and the presence of other beneficial nutrients. Soybeans are also one of the most folate-rich foods and rich in other B vitamins [43,44]. The macronutrients (per 100 gr) are calories (122 kcal), water (69.05 gr), protein (13.09 gr), carbohydrates (9,57 gr), fat (6.7 gr), and dietary fiber (1.1 gr).…”
Section: Legumes and Beansmentioning
confidence: 99%